ORCA-funded scuba certification for underwater archaeology: the Spanish Oristano Archaeology Project in Bluefields, Jamaica, 2019 - Risner, Lacy (Murray State's Digital Commons, 2019)
The Office of Research and Creative Activities awarded me a research grant to fund scuba certification at Mermet Springs, Illinois, allowing me to participate in underwater archaeological training during the 2019 field school in Bluefields, Jamaica. As an aspiring archaeologist, it is required to take a course in archaeological field methods. This particular field school offered the rare opportunity to acquire underwater archaeological training. The funding, provided by the Office of Research and Creative Activities, gave me the opportunity to acquire skills to further my future career and to contribute more context to the overall. The goal of the project was to determine if the Oristano estate, situated on high bluff just off the shore of the Bluefields Bay, was one of the initial Spanish settlements on the island. Since the previous underwater survey of the Bluefields Bay was conducted in 2008 with snorkels, we wanted to relocate the cannons and anchors that were previously documented. This would confirm their presence and indicate a potential location to survey for other artifacts, as well as allowing various training in searching and recording methods of underwater archaeology. One of the anchors that was relocated resembles an “Admiralty old patterned long shank” anchor with a timber stock, which correlates with the timeline the ceramic assemblage presents. The ceramic evidence from the terrestrial excavation indicated a strong British colonial presence that obscured the potential for finding very many artifacts from an earlier Spanish occupation. Further research and surveying are needed to make a firm determination.